2011
DOI: 10.1177/0003319710395558
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Long-Term Outcomes of Minor Lower Limb Amputations: A 5-Year Study

Abstract: Our aim was to assess the long-term outcome for minor forefoot amputations. A retrospective study of 126 patients who had such amputations between 1999 and 2004 was performed. Patients were divided into 2 groups, diabetic (group A: 79 patients) and nondiabetic (group B: 47 patients). Angiograms were requested in 45 patients in group A compared with 31 patients in group B (P = ·77). In group A, 11 patients underwent further ipsilateral amputations compared with 30 patients in group B (P = ·02.). The 2 groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We thought that it might be appropriate to refresh this with the best available data as they currently exist. Since that time, more reports have emerged both on cancer mortality [11] and mortality associated with DFU, [12][13][14] Charcot arthropathy, [15][16][17] and diabetes-associated lower extremity amputation [18][19][20][21][22][23][24][25][26][27]. We collected data containing 5-year mortality from studies published after the previous publication in 2007 and calculated a pooled mean.…”
mentioning
confidence: 99%
“…We thought that it might be appropriate to refresh this with the best available data as they currently exist. Since that time, more reports have emerged both on cancer mortality [11] and mortality associated with DFU, [12][13][14] Charcot arthropathy, [15][16][17] and diabetes-associated lower extremity amputation [18][19][20][21][22][23][24][25][26][27]. We collected data containing 5-year mortality from studies published after the previous publication in 2007 and calculated a pooled mean.…”
mentioning
confidence: 99%
“…Trends in amputation type discussed in our study played a significant role because minor amputations showed a lower rate of postoperative mortality compared to major amputations. Compared to an overall 5-year mortality rate of 30% to 40% following major amputation, a 27% overall 5-year mortality rate was reported in patients undergoing minor amputation 17. As the majority of patients scheduled for amputation exhibit comorbid conditions such as ischemic heart disease, stroke, and renal impairment, they are vulnerable to operations.…”
Section: Discussionmentioning
confidence: 98%
“…A diabetic foot ulceration (DFU) multidisciplinary team approach is highly recommended and has been shown to be the most effective strategy for reducing the rates of amputation and mortality in diabetic foot disorders ( 6 , 7 ). Ideally, this team should include a diabetologist, podiatrist, infectious disease specialist, orthopedic surgeon, vascular surgeon, physiotherapist orthotist, diabetes nurse, and an interventional radiologist ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%